Policy transparency in the public sector: The case of social benefits in Tanzania - Gemma Clare Wright; Vincent Leyaro; Elineema Kisanga; Christine Byaruhanga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
A well functioning system of public service delivery requires the definition and measurement of eligibility for services to be determined in a transparent and non-discretionary manner. This paper uses the case of the Productive Social Safety Net in mainland Tanzania to explore factors that hinder the achievement of this objective. The eligibility criteria for the Basic Cash Transfer and Variable Cash Transfer benefits are presented, and four aspects of the eligibility criteria are highlighted that compromise transparency: community targeting, the proxy means test, the imposition of conditionalities, and the fluid nature of the eligibility documentation. The issues were encountered during the design phase of a tax and benefit microsimulation model for Tanzania and all pose challenges for policy transparency. The authors argue that there are many ways in which transparency and clarity can be enhanced in relation to social benefit policy design and implementation, and that such improvements will greatly assist the public sector in ensuring that people in Tanzania receive the support they need.
Keywords: H83; I38; 330; transparency; social assistance; community targeting; Tanzania; microsimulation